An Overview of Nanogel Drug Delivery System - Farhana Sultana, Manirujjaman, Md. Imran-Ul-Haque, Mohammad Arafat, Sanjida Sharmin (Journal of Applied Pharmaceutical Science, 2013)
Nanogels based materials have high drug loading capacity, biocompatibility, and biodegradability which are the key points to design a drug delivery system effectively. The pursuit of this review article is to concisely describe the recent development of nanogel drug delivery system in terms of drug loading and swelling of drug from nanogels. Furthermore, biomedical application and current clinical trial studies of nanogel are summarized briefly. Here, different types of nanogels along with the synthetic procedure and mechanism of drug release from nanogel carrier are mainly focused. An intensive study of clinical trial in future will confirm nanogel as a suitable carrier for drug delivery.
Keywords: Nanogels, drug delivery, clinical trial, release mec